Transfer of Thinopyrum elongatum chromosome-specific 1EL.1AS translocation to hard wheat could not improve targeted bread-making quality - Failure and lessons learned. (September 2021) - Kumar, Aman; Chunduri, Venkatesh; Sharma, Saloni; Kumar, Ashish; Kumari, Anita; Kapoor, Payal; Kaur, Satveer; Garg, Monika
Abstract: The end processing quality of bread wheat is affected by several parameters such as grain texture, grain protein content, and gluten protein composition. Gluten proteins (glutenins and gliadins) are associated with bread-making quality, and among gluten proteins, high molecular weight-glutenins (HMW-GS) are considered the major determinant of bread-making quality. Wild varieties of wheat serve as sources of the novel HMW-GS alleles that can be explored to improve wheat processing quality. HMW-GS specific to one such wild relative of wheat Thinopyrum elongatum has been reported to enhance the processing quality in the background of soft textured Japanese cultivar Norin61 . In this study, we tried to transfer HMW-GS from Th. elongatum to hard textured, high yielding Indian cultivar PBW621. Two lines with different seed textures (Hard-TL and Soft-TL) were developed carrying 1EL.1AS translocation in PBW621 background. The effect of 1EL.1AS translocation on various quality parameters and bread-making quality was studied. Dough mixing properties, extensibility properties, and other quality parameters improved in hard and soft translocation lines. Comparing bread loaf volumes and bread quality scores suggested no significant differences in the improvement in individual quality parameters. Graphical abstract: Image 1 Highlights: M.A.S. based transfer of 1EL.1AS translocation to Indian cultivar PBW621. Successful transfer of Th. elongatum specific HMW glutenins to wheat. Development of two translocation lines with different grain textures. SSR based background screening of two lines suggesting good background recovery. Positive effect on individual quality parameters not reflected in terms of dough volume.